Health Outcomes Used to Determine Facets of Health-related Quality of Life for Post-9/11 Veterans Using Assistive Technology for A Combat-related Mobility Impairment: A Literature Review. Issue 11 (4th February 2021) - Greenhalgh, Mark; Kulich, Hailee; Blaauw, Eline; Turner, Rose; Peterson, Sara; Cooper, Rory A; Songer, Thomas
ABSTRACT: Introduction: Novel rehabilitation methods, including distribution and adoption of assistive technology for lower extremity impairments, are becoming crucial to ensure positive quality of life in all individuals. The quality of life of post-9/11 combat veterans is not well understood, in comparison to research on other populations. The following essay describes a review on health outcomes used to determine health-related quality of life (HR-QoL) among combat-injured service members who require mobility-related assistive technology. Materials and Methods: Reviews pooled data from research on PubMed, EMBASE, CINAHL, and PsycINFO published after September 11, 2001, and included service members who sustained a mobility impairment because of involvement in a post-9/11 combat operation. Basic descriptors were extracted in addition to health outcomes used, which were then categorized and summarized by six domains for HR-QoL as defined by the World Health Organization. Results: This review found health outcomes that fit in the pain and discomfort, negative emotions, mobility, social relations, access to and quality of healthcare services, and religious/spiritual/personal beliefs subdomains. The categorized results detailed their application to track and model HR-QoL health states in those with mobility impairments using mobility-based assistive technology. Conclusions: The research on combat-induced mobility impairments indicates assistive technology improves otherwise poor health states. The results model these domains and subdomains to determine overall HR-QoL and the quality of a healthcare intervention, though additional research is needed as only one study was identified to be experimental in design.